Chapter Two: The Weight of Past Historiography and the State of the Question: Early Protestant Apologias and Denials. - Benedict, Philip (Transactions of the American Philosophical Society, 2020)
Calvin and Beza in Geneva also did their utmost after the conspir- acy's failure to squelch rumors that they had supported the venture, to downplay their prior knowledge of it, and to minimize the participa- tion of Geneva's larger exiled French community. Calvin's longest self-justification, and the letter most often cited by subsequent historians as evidence of his attitude toward the conspirJ J CO, xvni, col. 39, Calvin to Sturm, Geneva, March 23, 1560: "Quum me principio consulerent qui primi ad hoc negotium agitandum aliis fuerunt autores, libere respondi, mihi non placere totam agendi rationem, rem vero ipsam multo minus probari. They chose as their leader La Renau- die, "a man of great spirit and almost incredible energy", and sur2 5 Brieve remonstrance des Estats de France, Au Roy leur souverain seigneur, sur I' ambition, tyrannie et oppression du tout intolerable des de Guyse\ Briefve exposition des Lettres du Cardinal de Lorraine envoyees au nom du Roy aux Cours des Parlemens de France, Response ebretienne et defensive sur aucuns points calomnieux contenus en certaines lettres envoyees aux baillis, senechaux et lieutenants du Roy, L ' Histoire du tumulte d' Amboise. PAST HISTORIOGRAPHY AND THE STA TE OF THE Q UESTION 17 The March 31 account was extremely important for shaping the subsequent understanding of the conspiracy of Amboise.